(untitled) - Dalgic, Tevfik; Yeniceri, Tulay (Business Expert Press, 2013)
Ebook from IG Library ; This book is about customer orientation as a marketing strategy. It covers the vast literature on the subject and tries to combine the major studies in this specific field of marketing and strategy to offer a comprehensive strategic tool for decision makers in organizations. The book starts with the classic marketing concept and then reviews important developments and research of the latest findings both from the theoretical and applied points of view. Examples, methodologies, policy measures, and strategies to be implemented in order to drive customer satisfaction are the backbone of this book. Both manufacturing and service businesses are addressed. This book also covers the relationships, applications, and steps to be taken to drive continuous relationships with customers to aid in the process of defining and implementing niche strategies, international marketing efforts, and electronic commerce.
Keywords: Marketing Strategy ; Quản lý tiếp thị; Chiến lược tiếp thị